Bumpless switching control for switched systems with partial actuator failures. Issue 15 (17th November 2016) - Qi, Yiwen; Bao, Wen; Zhang, Qingxin; Chang, Juntao
ABSTRACT: This study is concerned with the bumpless transfer problem for switched systems with partial actuator failures, in order to obtain smooth system performance output transition. Taking into account that the system requires a controller switching from current sub-controller to a fault-tolerant sub-controller after actuator fault. And bumpless transfer for control input cannot be traditionally designed when the actuator fault occurs, while performance smoothing can be considered and it is actually the ultimate goal of bumpless transfer. Specifically, the actuator fault model is firstly established and partial actuator fault is considered. Then, the system performance output signal is deemed as the main design variable of bumpless transfer, and closed-loop control systems both previous and after controller switching are constructed. Moreover, by using model matching thought and the adaptive sliding mode control technique, a bumpless transfer compensator design strategy is given to drive the performance output variable (after controller switching) to track the one of reference model. At last, simulation results of numeric and application examples demonstrate the effectiveness of the proposed bumpless transfer strategy.